Wybrane oprawy ksiąg z prywatnych bibliotek polskich w zbiorach kanonika gnieźnieńskiego Tomasza Josickiego - Muraszko, Michał (Studia Europaea Gnesnensia, 2015)
The article presents selected book bindings from the collection of a Gniezno canon, Tomasz Josicki, which originally belonged to three private libraries.